Answer:
x = 13/6
Step-by-step explanation:
We are the following expression;
x - 2(2 - (3/2)*x) = 2(4 - x) + 1
x - (4 - 3*x) = 8 - 2*x + 1
x - 4 + 3*x = 8 - 2*x + 1
4*x + 2*x = 9 + 4
6*x = 13
x = 13/6
The answer is c 109 degrees
Answer:
30 years
Step-by-step explanation:
41 minus 11=
5+7+11=23
3+11+53=67
3+11+61=71
are some examples
1st year 500* 0.03 = 15+500=515
2nd year 515*0.03= 15.45 + 515 = 530.45
3rd year 530.45*0.03= 15.9135 + 530.45 = 546.3635
4th year 546.3635 * 0.03 = 16.390905 + 546.3635 = 562.754405
562.754405